O Hospital e Asilo da Venerável Ordem Terceira de S. Francisco de Coimbra : fundação e adaptação dos espaços (1851-1910) - Silva, Ana Margarida (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
This paper attempts to address the origins of the Hospital and Asylum of the Venerable Third Order of Coimbra, Portugal: how and why it was founded (in 1851 and 1884), the adaptation of spaces to assistance functions and its regulations, seeking, whenever possible, giving standard and exceptional examples in order to illustrate the behavior of the Hospital and the Asylum between 1851 and 1910. Since early times their ministers and other members of the Definitory had a founding dream of the implementation of an hospital dedicated exclusively to the secular Franciscan brothers. It was only possible in 1845 with the donation of the Carmo building, localized in Sofia street.